Transformations of Disgust in Interaction - Sally Wiggins; Leelo Keevallik (Social Interaction, 2023)
Expressions of disgust have typically been studied as isolated faces or voices but rarely as embodied practices in everyday interaction. Building on multimodal interactional research on emotions and sensoriality, this paper addresses disgust as a unique topic at the intersection between psychological theory and interactional facts. A case of an adult enacting post-consumption disgust is analysed, detailing the transformation of the facial, auditory, and embodied expressions across interactional sequences and in collaboration with others. The paper showcases the variability of disgust expressions and their involvement in social actions such as displaying stamina or stoicism toward challenges.